PERAN BAHASA DALAM PEMAHAMAN ANTARBUDAYA - Nugrahani, Farida (STILISTIKA, 2012)
PERAN BAHASA DALAMÂ PEMAHAMAN ANTARBUDAYAFarida NugrahaniProgram Pascasarjana Magister Pendidikan Bahasa Indonesia (S2) Univet Bangun NusantaraJl. S. Humardani Jombor Sukoharjo Ponsel: 081226229733 Pos-El: farida_nugrahani@yahoo.comÂ ABSTRACTLanguage is a culture system and a socio cultural phenomena which is never free from the community user. Since a language is not only as mean of communication and socialization but also asÂ the mirror of the culture of the community of the users. Language has an the important role the help the process of understanding, because it always gives the sign of idea, spiritual atmosphere, ethic, aesthetic, and social regulation of the community when the language users live in. It means that language and culture have a strong relationship. We can use a the language for positive or negative things that effect the harmony of the relationship between a person and community. It is the reason that a person needs to learn a language especially speech act in order that he can use the language properly.Keywords: Language, understanding process, socio culture system.